The Relationship between Sports Participation and Internet Addiction among University Students of Shahrekord City - Zahra Rahimi-Rigi; Mohammadreza Moradi; Alireza Omidi (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Internet addiction among young people and especially university students has become a major social problem. The positive social and psychological effects of participation in sports activities could potentially compensate the harmful effects of addiction to the Internet. The objective of this study was to investigate the relationship between participation rate in sports activities and Internet addiction among university students in Shahrekord city. Materials and Methods: This field study was of correlational design. The statistical population of the study included university students of universities in Shahrekord including Shahrekord University, Azad University, Applied Sciences University, Medical Sciences University, Technical University and Payame Noor University. Approximately 24,300 students studied in the academic year 2017-2018, among whom, 379 students were randomly selected. Data were collected using a demographic questionnaire, a researcher-made questionnaire on participation in student sports activities in terms of minutes per week, and the Young's Internet Addiction Inventory. Data was analyzed using Pearson correlation coefficient in SPSS software. Results: Participants included 188 (49.6%) male and 191 (50.4%) female students. Increased sports participation score with mean (SD) 105.3 (8.3) was associated with decreased Internet addiction score 2.2 (0.8) Internet addiction, P<0.05. In addition, the sports participation variable has the predictive power over Internet addiction, as increasing one unit in the variable of sports participation, Internet addiction decreased by 0.33 units. Conclusion: The study showed that participation in sport activities was had a positive impact on reduced rate of Internet addiction among university students in Shahrekord. DOI: http://doi.org/10.22037/ch.v6i4.24522